Training Educational Assistants to Facilitate Grammatical Development of Adolescents Who Use AAC - Eckdahl, Hallie G. (My University, 2018)
In 2016, the American Speech-Language Hearing Association (ASHA) surveyed school-based speech-language pathologists (SLPs) and found that approximately 55% served students who used some form of augmentative and alternative communication (AAC) (ASHA Schools Survey). AAC offers the potential for individuals with complex communication needs (CCN) to enhance communication, improve academic achievement, and increase societal participation. Unfortunately, many students lack access to effective AAC interventions due to lack of practicing SLPs with experience in AAC (ASHA, 2010), as well as a lack of training for key stakeholders (e.g. parents, teachers, educational assistants). Costigan and Light (2010) noted that many clinicians and special education teachers receive little to no pre-service exposure to AAC. In many schools across America, educational assistants (EAs) may spend the most amount of time supporting students who use AAC, but receive the least amount of formal training (Kent- Walsh & Light, 2003). While there is a growing body of research evidence that suggests that EAs can be trained to support the communication of young children with CCN, there is a notable gap with adolescent students (Binger, Kent-Walsh, Ewing, & Taylor, 2010; Douglas, Light, & McNaughton, 2012; Kent-Walsh, 2003). Therefore, the current investigation sought to expand the research base in the area of partner instruction to evaluate the viability with an adolescent population of AAC users. The current investigation utilized a single-subject, multiple-baseline design across three dyads to examine the effects of training EAs to modify their interaction patterns during a curriculum based reading activity with the adolescent AAC user that they support. More specifically, the EAs were taught to use the Read-Ask-Answer-Prompt (RAAP!) interaction strategy (Binger et al., 2010) in order to facilitate their students’ use of grammatical morphology. Visual Analysis and effect size analyses indicated that the intervention was highly effective at increasing the EAs’ use of the target strategy, as well as the students’ correct production of grammatical morphemes. These findings suggest that an effective communication partner training program can lead to EA instructional gains, as well as communication gains for adolescents who use aided communication. The results, clinical and educational implications, and future directions are discussed.
I INTRODUCTION 1 -- II REVIEW OF RELATED LITERATURE 4 -- Communication and Language Development 4 -- Theoretical Frameworks for Language Acquisition in AAC 8 -- Aided Language Production 9 -- Demands on Learning Mechanisms/Access Barriers 10 -- Working memory and attention demands 10 -- Opportunity Barriers to Language Acquisition 12 -- Contingent responsivity 12 -- Creating an Alternate Path to Language Learning in AAC 14 -- Assessment of Children with Spoken Language Disorders 15 -- Functional Assessment of School-Age and Adolescent Populations 15 -- Functional Assessment of Students Who Require AAC 17 -- The participation model 19 -- Intervention Approaches for Children with Spoken Language Disorders 20 -- Clinician-Directed Approaches 21 -- Child-Centered Approaches 22 -- Hybrid Approaches 23 -- Language Intervention Approaches for Students with Complex Communication Needs 25 -- Explicit Instruction and Incidental Teaching 26 -- Strategy Instruction Model (SIM) 27 -- Language Modeling Techniques 27 -- School-based Functional Interventions 29 -- Agents of intervention 31 -- Intervention Strategies for Students who Require AAC 32 -- Naturalistic Instruction 32 -- Integrated Approaches 33 -- Communication Partner Instruction 34 -- Limitations and gaps 38 -- ImPAACT program 39 -- Significance of the Problem 40 -- Purpose of the Study 41 -- Conclusions 41 -- III METHODOLOGY 43 -- Research Design 43 -- Participants 44 -- Educational Assistant (EA) Participants 44 -- EA selection criteria 44 -- Student Participants 44 -- Student participation criteria 44 -- Screening of student skills 45 -- Dyad Profiles 46 -- Dyad 1 (Anita and Alex) 46 -- Dyad 2 (Brooke and Brianna) 48 -- Dyad 3 (Cassie and Cole) 49 -- Setting 51 -- Instrumentation 51 -- Procedures 53 -- Baseline 55 -- Instruction and Intervention 55 -- Instruction content 55 -- Instruction format 57 -- Intervention 58 -- Maintenance 59 -- Data Analysis/Measures 59 -- Data Collection/Coding 60 -- Visual analysis of data 60 -- Interrater/Coding reliability 61 -- Procedural Fidelity 61 -- Social Validity 62 -- IV RESULTS 63 -- Participant Analysis 63 -- EA Participant Analysis 63 -- Student Participant Analysis 64 -- Social Validation 69 -- Educational Assistant Questionnaire 69 -- Teacher Questionnaire 69 -- V CONCLUSION 71 -- Effectiveness of Instructional Program to Increase Targeted Strategy Use 71 -- Comparisons to Results of Past Communication Partner Research 72 -- Effects of Strategy Use on the Students’ Grammatical Morpheme Productions 73 -- Strategy Instruction Model 73 -- Aided AAC Modeling 75 -- Implications of Findings 77 -- Limitations 78 -- Recommendations for Future Research 79 -- Conclusions 80 -- REFERENCES 81 -- APPENDIX A: Institutional Review Board Approval Letter 102 -- APPENDIX B: Social Validity Measures and Results 104 -- APPENDIX C: News-2-You™ Articles and Communication Display 110 -- APPENDIX D: Data Collection Forms 120 -- APPENDIX E: Participant Demographic Questionnaires 123 -- APPENDIX F: Communication Partner Observation Tool 129 -- APPENDIX G: Visual Aid for Target Interaction Strategy 131 -- APPENDIX H: EA Training Program 133 -- APPENDIX I: Implementation Sequence for Target Interaction Strategy 136 -- APPENDIX J: Fidelity Checklist 138 -- APPENDIX K: Instructional Program Contract 143.
Keywords: Dissertations, Academic--United States; American Speech-Language-Hearing Association; People with disabilities--Means of communication; Speech therapists